An Efficient Synthesis of Nitrated Cycloalka[b]pyridines - Le, Song Thi; Asahara, Haruyasu; Nishiwaki, Nagatoshi (Synthesis, 2014)
The three-component ring transformation of 1-methyl-3,5-dinitro-2-pyridone with cycloalkanones of different ring sizes in the presence of ammonium acetate affords the corresponding nitrated cycloalka[b]pyridines in high yields. Furthermore, a double bond can be easily introduced into the product by changing the cycloalkanone into a cycloalkenone.
Keywords: pyridines; multicomponent reaction; ketones; heterocycles; bicyclic compounds; ring transformation